Neuroblastoma and Hippo Signaling Pathway - Selen Kum Özşengezer; Zekiye Altun; Nur Olgun (Galenos Publishing House, 2021)
Neuroblastoma (NB) is a malignant tumor often seen in early childhood and originating from the sympathetic nervous system.Hippo signal pathway is a mechanism involved in organ growth, differentiation and plays an important role in stem cells, cancer stem cells and tumorigenesis.YAP,which is the transcription co-activator, is an important part of this mechanism and the inhibition effect of YAP inhibition on cell proliferation highlights the effect of this pathway on cancer. In the diagnosis and prognosis of pediatric tumors, more beneficial clinical applications of YAP and other routes can be considered and further research can be expected.Hippo pathway members, especially YAP, are potential new treatment targets for tumors that show overexpression. Along with the clinical features that affect the progression of the NB, chromosomal abnormalities and both oncogenes and tumor suppressor genes need to be evaluated together to develop new treatment strategies, especially in aggressive NB's. In recent studies, YAP inhibition has been shown to impair tumor growth and NB's cisplatin resistance.This defines YAP as a potential therapeutic target, especially for cisplatin-resistant NB.Hippo is a new glimmer of hope for NB in the signal pathway and open to study and development since all steps cannot be actively determined.